Updated Measurements of [O iii] 88 μm, [C ii] 158 μm, and Dust Continuum Emission from a z = 7.2 Galaxy - Yi W. Ren; Yoshinobu Fudamoto; Akio K. Inoue; Yuma Sugahara; Tsuyoshi Tokuoka; Yoichi Tamura; Hiroshi Matsuo; Kotaro Kohno; Hideki Umehata; Takuya Hashimoto; Rychard J. Bouwens; Renske Smit; et al. (The Astrophysical Journal, 2023)
We present updated measurements of the [O iii ] 88 μ m, [C ii ] 158 μ m, and dust continuum emission from a star-forming galaxy at z = 7.212, SXDF-NB1006-2, by utilizing Atacama Large Millimeter/submillimeter Array (ALMA) archival data sets analysed in previous studies and data sets that have not been analysed before. The follow-up ALMA observations with higher angular resolution and sensitivity reveal a clumpy structure of the [O iii ] emission on a scale of 0.32–0.85 kpc. We also combined all the ALMA [O iii ] ([C ii ]) data sets and updated the [O iii ] ([C ii ]) detection to 5.9 σ (3.6 σ –4.5 σ ). The non-detection of [C ii ] with data from the REBELS large program implies the incompleteness of spectral-scan surveys using [C ii ] to detect galaxies with high star formation rates (SFRs) but marginal [C ii ] emission at high- z . The dust continuum at 90 and 160 μ m remains undetected, indicating little dust content of <3.9 × 10 ^6 M _⊙ (3 σ ), and we obtained a more stringent constraint on the total infrared luminosity. We updated the [O iii ]/[C ii ] luminosity ratios to 10.2 ± 4.7 (6.1 ± 3.5) and 20 ± 12 (9.6 ± 6.1) for the 4.5 σ and 3.6 σ [C ii ] detections, respectively, where the ratios in the parentheses are corrected for the surface brightness dimming effect on the extended [C ii ] emission. We also found a strong [C ii ] deficit (0.6–1.3 dex) between SXDF-NB1006-2 and the mean L _[C _II _] −SFR relation of galaxies at 0 < z < 9.